Pelaksanaan Pemerintahan Desa Berdasarkan Prinsip Good Governance - Khoiriah, Siti (Faculty of Sharia, Institut Agama Islam Negeri (IAIN) Metro, Lampung, Indonesia., 2022)
Abstract Good governance as part of the reform agenda is basically a condition that is aspired to in every aspect of government that interacts with society, especially rural communities. This highly aspired condition is based on an understanding of the principles that apply good governance, including: accountability, transparency, transparency, rule of law, justice, participation, decentralization, togetherness, professionalism, responsiveness, effectiveness and efficiency, and competitiveness. All of this illustrates that the character of the village as a self-governing community is much broader and more capable. The main task carried out by the village government is to create a democratic life, to provide good social services so that it can bring its citizens to a prosperous, peaceful, and just life. This leads to the practice of village good governance in Indonesia. Key words: good governance, and village.